2016
DOI: 10.1038/srep28331
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fission is an acute and adaptive response in injured motor neurons

Abstract: Successful recovery from neuronal damage requires a huge energy supply, which is provided by mitochondria. However, the physiological relevance of mitochondrial dynamics in damaged neurons in vivo is poorly understood. To address this issue, we established unique bacterial artificial chromosome transgenic (BAC Tg) mice, which develop and function normally, but in which neuronal injury induces labelling of mitochondria with green fluorescent protein (GFP) and expression of cre recombinase. GFP-labelled mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 58 publications
2
64
0
Order By: Relevance
“…25 The Atf3 :BAC Tg mouse expresses GFP specifically in injured neurons, which mimics transcriptional regulation of Atf 3. Because the mitochondrial targeting signal is attached to GFP in the mouse, the GFP is imported into mitochondria immediately after synthesis, resides in the soma, and is transported into axonal tips and dendrites.…”
Section: Resultsmentioning
confidence: 99%
“…25 The Atf3 :BAC Tg mouse expresses GFP specifically in injured neurons, which mimics transcriptional regulation of Atf 3. Because the mitochondrial targeting signal is attached to GFP in the mouse, the GFP is imported into mitochondria immediately after synthesis, resides in the soma, and is transported into axonal tips and dendrites.…”
Section: Resultsmentioning
confidence: 99%
“…2 A – E ). Increased fission is a behavior associated with mitochondrial biogenesis (21) and previously observed in regenerating axons (22, 23). …”
Section: Resultsmentioning
confidence: 85%
“…As described above, these intriguing morphological changes of mitochondria in Drp1 CKO injured neurons were seen at 1wk after injury. The previous reports using the same Drp1‐deficient model (Kiryu‐Seo et al, ) showed decreased mitochondria integrity, including reduced membrane‐potential detected in injured axon with marker TMRM, and in injured soma with accumulation of Parkin, a maker for dysfunctional mitochondria (Narendra, Tanaka, Suen, & Youle, ). Therefore, it is likely that the mitochondrial morphological changes of Drp1 CKO mice shown in this study were correlating with the mitochondrial function to some extent.…”
Section: Discussionmentioning
confidence: 83%
“…The present FIB/SEM technology allows for the reconstruction of 3D images of organelles; the images of several hundreds of serial sections can be obtained by SEM and the resolution of these images are comparable to those obtained with TEM. After examining 3D morphologies of somatic mitochondria of motor neurons before and after nerve injury using FIB/SEM, we found no significant changes in morphology of somatic mitochondria, although the size of axonal mitochondria became smaller (Kiryu‐Seo et al, ). Drp1 deficiency in injured motor neurons, however, induced drastic changes of somatic mitochondrial morphology as well as the degeneration of mitochondria demonstrating huge spheroidal morphology with local or total cristae collapse, and mitophagy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation